2019
DOI: 10.1002/adfm.201908242
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Photonic Microbricks via Crack Engineering of Colloidal Crystals

Abstract: Evaporation-induced self-assembly of colloidal particles is one of the most versatile fabrication routes to obtain large-area colloidal crystals; however, the formation of uncontrolled "drying cracks" due to gradual solvent evaporation represents a significant challenge of this process. While several methods have been reported to minimize crack formation during evaporation-induced colloidal assembly, here we report an approach to take advantage of the crack formation as a patterning tool to fabricate microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…Faster condensate removal through the cracks refreshed the surface and prepared it for renewed droplet nucleation and growth. These results suggest that hierarchical (two-level) porosity, which can be achieved by engineering cracks in colloidal crystals, 32 has a potential for faster condensate removal that can translate to improved phase-change condensation heat transfer rate.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Faster condensate removal through the cracks refreshed the surface and prepared it for renewed droplet nucleation and growth. These results suggest that hierarchical (two-level) porosity, which can be achieved by engineering cracks in colloidal crystals, 32 has a potential for faster condensate removal that can translate to improved phase-change condensation heat transfer rate.…”
Section: Resultsmentioning
confidence: 90%
“…Using the bottom-up colloidal co-assembly technique, [30][31][32] we coated copper tubes (length = 60 mm, external diameter = 6.35 mm, internal diameter = 4.57 mm) with silica inverse opals; a highly porous material consisting of sub-micron voids in a support matrix (see materials and methods for material synthesis and sample fabrication). Typical scanning electron micrograph (SEM) images of the porous inverse opal coating at different magnifications are shown in Fig.…”
Section: Sample Fabricationmentioning
confidence: 99%
“…The measured reflectance values of silica colloidal crystals stacked at different rotational speeds (150, 200, and 250 rpm) and radii of rotation (8,16,24,32, and 40 cm) are presented in Figure 2. The concentration of the colloidal silica solution was 30 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…The two glass plates were treated to possess hydrophobic and hydrophilic properties, respectively, to allow the colloidal crystals to easily remain on the hydrophilic-treated glass plate [26]. These glass plates were fixed by magnets and placed in humid dishes that were placed at various positions (8,16,24, 32 and 40 cm) on the rotator, as shown in Figure 1. The positions of the samples were defined by their distances from the rotating axis.…”
Section: Methodsmentioning
confidence: 99%
“…[ 15,16 ] Therefore, most of previous efforts were devoted to circumventing them. [ 15,17,18 ] Recently, it has been demonstrated that regulated crack patterns could be useful in some applications, such as fabrication of microchannels, [ 9,19 ] photonic microbricks, [ 20 ] and sensors, [ 21 ] due to their excellent controllability of morphology and periodicity. Herein, we utilized rational designed cracks to obtain uniform CRs.…”
Section: Figurementioning
confidence: 99%